Assessing the Impact of the Family Hope Program on Mitigating Economic Underdevelopment in Berastagi City - Simarmata, Nefri Laila; Siahaan, Jadi Hatoguan (Law and Economics, 2022)
This research investigates the effectiveness of the Family Hope Program (FHP) as a strategy to mitigate economic underdevelopment in Berastagi City, North Sumatra, Indonesia. Employing a mixed-methods approach, the study evaluates the FHP's impact on economic indicators, human capital development, and community engagement. Quantitative data, gathered through structured surveys among program beneficiaries, is complemented by qualitative insights from interviews and case studies. Findings indicate notable improvements in household income, access to education, and healthcare services among beneficiaries. The program's emphasis on community engagement and holistic support fostered a sense of empowerment and social cohesion within the community. However, challenges persist, including limited economic diversification and infrastructural deficiencies. Recommendations underscore the need for economic diversification, infrastructure development, and community-driven initiatives to enhance program effectiveness. Contextualized within existing developmental theories, the conclusions drawn advocate for adaptive strategies and collaborative efforts to foster sustainable socio-economic development. This research provides insights guiding policymakers and stakeholders in shaping targeted interventions for inclusive and resilient development in Berastagi City.